Células endoteliais humanas (HUVEC) infectadas por Toxoplasma gondii modulam funções biológicas de células trofoblásticas extravilosas humanas (HTR-8/SVneo) - Guirelli, Pâmela Mendonça (2019)
The interaction between human extravillous trophoblast and human endothelial cells has an important role in embryonic implantation and placentation. Changes in communication patterns between these two cell populations are associated with pregnancy complications, in this context, Toxoplasma gondii infection can be a potential problem in this crosstalk. Therefore, the aim of this study was to evaluate the occurrence of invasion, migration and cell death of extravillous trophoblast cells (HTR-8/SVneo cell line) under influence of infected human venous endothelial cell (HUVEC) by T. gondii. HTR-8/SVneo cells were co-cultured with T. gondii-infected or uninfected HUVECs in order to analyze cytokine production by ELISA as well biological functions of extravillous trophoblast cells. The invasive capacity of trophoblastic cells was analyzed using transwell inserts previously covered with Matrigel, the migratory capacity of these cells was verified by scratch method and the cell death index was measured by the flow cytometry. HTR-8/SVneo cells and HUVECs interaction induced secretion of IL-6 and IL-8 by trophoblastic cells. MIF secretion was downregulated by HTR-8/SVneo cells after co-culture with uninfected HUVECs, but upregulated MIF levels were detected after co-culture with infected HUVECs. Stimuli of uninfected HUVECs co-culture reduced invasive capacity and increased migration of HTR-8/SVneo cells. Otherwise, infected HUVECs condition enhanced invasive capability, reduced migration, induced cell death index of trophoblastic cells. The treatment with ISO-1, highly specific MIF inhibitor, altered the events related to invasive capacity and cell death of HTR-8/SVneo when compared to each conditions without treatment with MIF inhibitor. The extravillous trophoblast-venous endothelial cells crosstalk was changed by T. gondii infection and induction of MIF production by HTR-8/SVneo cells together with changes in cell death index, might be some of the factors responsible for alteration in trophoblastic functions related to migratory and invasive capacity of extravillous trophoblastic cells.